Chinese functional foods and nutraceuticals: plants and products commercialized in the Ciudad Autónoma de Buenos Aires, Argentina - Puentes, Jeremías Pedro; Arenas, Patricia Marta; Hurrell, Julio Alberto (Ethnobiology and Conservation, 2019)
This article contributes to the study about urban botanical knowledge within the pluricultural context of Buenos Aires-La Plata Metropolitan Area, in particular, the botanical knowledge about plants and its products introduced by Chinese immigrants in the Ciudad Autónoma de Buenos Aires. The registered functional food and nutraceutical plants products marketed by these immigrants (that belong to the Traditional Chinese Phytotherapy) are locally employed for the treatment of diseases linked to the urban way of life, such as diabetes, hypercholesterolemia, hypertension, cancer, cognitive dysfunctions, among others. In this sense, the work contributes to the understanding of the local biocultural diversity (both plants and its associated knowledge). The research followed usual qualitative ethnobotanical methods and techniques, especially semi-structured and free interviews to 250 qualified informants, prior informed consent. An inventory of plant products of 52 vascular plants (vegetables, legumes, fruits, condiments) locally recognized as functional foods was obtained. Plants products belonging to 30 of the 52 treated taxa are commercialized only within the restricted commercial circuit of the Chinese immigrants. Therefore, these taxa are considered “invisible” for the majority of local inhabitants. Plants products of the 22 remaining taxa are marketed in both the restricted Chinese circuit and the general commercial one. Then, these taxa are “visible” for all residents. Local botanical knowledge is evaluated from the circulation of plant products in local trade circuits. “Invisible” taxa may become “visible” when entering the general commercial circuit. This “visualization process” of plants products and its associated knowledge express the local botanical knowledge dynamics.